Pemberian Pelatihan Analisis Butir Soal Bagi Guru di Kabupaten Jombang : Efektif? - Kurniawan, Riza Yonisa; Fiky Prakoso, Albrian; Hakim, Luqman; Mustika Dewi, Retno; Widayanti, Irin (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
Teacher's unfamiliarity in analyzing items is one of the factors causing teacher to be reluctant to do item analysis. While the item analysis is needed to establish the problem as an evaluation tool to measure the level of students' understanding of the material being studied. The purpose of this training is to (1) provide teacher understanding about the item analysis (2) to provide assistance in analyzing the items, (3) to provide assistance to teachers in practicing the analysis of items using software anates. The subject of this study is the teacher of Vocational High School in Jombang regency. With object study training analsis item using Anates software. The results of the training were very effective as evidenced by the majority of participants being able to practice the item analysis, but some participants were reluctant to analyze the items due to age and lack of time and effort.